COMPARATIVE STUDY BETWEEN THREE COURTYARDS OF TRADITIONAL HOUSES IN ISLAMIC CAIRO - Wazeri, Yehia Hassan (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2013)
AbstractDirect solar radiation is considered the most important climatic element, which has direct and indirectinfluences on designing buildings and open spaces. In hot arid regions, like Cairo, the main aim is to reduce theheat load in summer, and to maximize it in winter. The aim of the present comparative study is to determine the shaded area and the quantity of direct solar radiation (on 21 June 21 December) fall on walls, floors and openings of three courtyards in traditional Islamic houses in old Cairo. For this purpose a network of three traditional courtyards houses has been selected in old Islamic Cairo. The first is Zaynab Khatun house (built1468AD), the second is Gamal Al-Din Al-Dahaby (built 1637AD), and the third is Es-Sinnari house (built 1794AD).Key words: courtyards; traditional houses; Islamic Cairo. AbstrakRadiasi matahari langsung merupakan elemen iklim yang paling penting untuk dipertimbangkan dalamperancangan, baik yang memberikan pengaruh langsung maupun tidak langsung pada perancangan bangunandan ruang terbuka. Di daerah kering dan panas, seperti halnya Cairo, beban panas di musim panas dikurangi dan dimaksimalkan di musim dingin. Tujuan dari penelitian yang menggunakan tiga studi banding ini adalah untuk menentukan daerah yang teduh dan melihat jumlah radiasi matahari langsung pada tanggal 21 Juni dan21 Desember, yang mengenai pada dinding, lantai dan bukaan yang bersumber dari halaman rumah tradisional Islam di kota tua Kairo. Untuk itu, telah dipilih tiga rumah tradisional di Kairo yang memiliki halaman yaitu rumah Zaynab Khatun yang dibangun pada 1468AD, kedua rumah Gamal Al-Din Al-Dahaby yang dibangun pada1637AD, dan yang ketiga adalah rumah Es-Sinnari yang dibangun pada 1794AD. Kata kunci: halaman, rumah-rumah tradisional, Islam Kairo.